Ultrasound-Assisted Extraction Optimization of Proanthocyanidins from Kiwi (Actinidia chinensis) Leaves and Evaluation of Its Antioxidant Activity - Ji-Min Lv; Mostafa Gouda; Yan-Yun Zhu; Xing-Qian Ye; Jian-Chu Chen (MDPI AG, 2021)
Using ultrasound (US) in proanthocyanidin (PA) extraction has become one of the important emerging technologies. It could be the next generation for studying the US mechnophore impact on the bioactive compound's functionality. The objective of this study was to demonstrate the potential of US treatment on PAs extracted from kiwifruit (Actinidia chinensis) leaves, and to provide a comprehensive chemical composition and bioactivity relationship of the purified kiwifruit leaves PAs (PKLPs). Several methods like single-factor experiments and response surface methodology (RSM) for the four affected factors on US extraction efficiency were constructed. HPLC-QTOF-MS/MS, cytotoxicity analysis, and antioxidant activity were also demonstrated. In the results, the modeling of PA affected factors showed that 40% US-amplitude, 30 mL/g dry weight (DW) solvent to solid ration (S/S), and 70 °C for 15 min were the optimum conditions for the extraction of PAs. Furthermore, PKLPs exhibited significant radical scavenging and cellular antioxidant activity (p < 0.05). In conclusion, this study's novelty comes from the broad prospects of using US in PKLP green extraction that could play an important role in maximizing this phytochemical functionality in drug discovery and food science fields.